Description of larvae and redescription of the fungus beetle Pselaphacus procerus Kuhnt, 1910 (Coleoptera: Erotylidae: Erotylinae: Tritomini) from Brazil - Casari, Sônia A.; Silva, Thiago J.; Polizei, Thiago T. S. (Zootaxa, 2024)
The early and mature larvae of Pselaphacus procerus Kuhnt, 1910 are described here for the first time and the adult male and female are redescribed. The description of the larvae of this species represents the second of Pselaphacus immatures. The early larvae of this species are easily separated from mature larvae, by the absence of dorsal sclerotized plates on the abdomen of the former. Based on observations and information from literature, we provide a synopsis of the larval studies on Erotylini, data on maternal behavior in the genus and an updated biogeographical distribution of this species.